Aconselhamento pastoral em casos de abuso sexual - Coelho, Ana Alice Teixeira de Lima (2010)
Sexual abuse is not only considered a crime before the law, is also a public-health problem, with both immediate and later-appearing effects on the victims which include physical, emotional, behavioral and spiritual problems. Society as a whole needs to join in a common effort to reduce the incidence of violence, and this type of problem needs to be addressed by people from several professions, in an interdisciplinary manner. The Christian church, as a social institution, must not abdicate this responsibility. Its role ranges all the way from raising the awareness of its members concerning the issue of violence, to the vitally important spiritual and emotional recovering of the victims across counseling pastoral. The present-day rediscovery of the power of small groups is one of the most promising areas of pastoral counseling. This approach involves not only the pastor but also committed and trained lay leaders, and also the entire congregation, thus making the whole church into an agent of change with regard to what is happening in society. In the experience of the Ágape Evangelical Baptist Community, group counseling has been an excellent tool for helping adults who in childhood were victims of sexual abuse. These groups apply the method of REVER Ministry, which uses the Twelve Steps of Alcoholics Anonymous, along with Bible study and the Nine Steps of Support Groups for Victims of Sexual Abuse, translated and organized by Deborah Kornfield, linked with the tools of faith imagination and prayer counseling. For the pastoral counseling of families, the Ágape Community has adapted the method of therapist Cloé Madanes, consisting of twenty steps which can be applied in a great variety of cases, providing support for the victim, his/her family members and the abuser. Doubtless these tools are not the only ones that produce results, so it would be helpful if the communities would make available their resources so that there could be an exchange of experiences, thus increasing even more the efficiency of their approaches that seek to diminish the negative impact of sexual abuse on society.